2022
DOI: 10.1029/2021gc010171
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Lithospheric Strength and Upper‐Plate Seismicity in the Southern Central Andes, 29°–39°S

Abstract: We examined the relationship between the mechanical strength of the lithosphere and the distribution of seismicity within the overriding continental plate of the southern Central Andes (SCA, 29°–39°S), where the oceanic Nazca Plate changes its subduction angle between 33°S and 35°S, from subhorizontal in the north (<5°) to steep in the south (∼30°). We computed the long‐term lithospheric strength based on an existing 3D model describing variations in thickness, density, and temperature of the main geological u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 143 publications
(235 reference statements)
4
10
1
1
Order By: Relevance
“…Our results confirm previous studies, indicating a southward decrease in upper‐plate seismicity (Gutscher et al., 2000; Nacif et al., 2017; Rodriguez Piceda et al., 2022). However, our updated and comprehensive analysis, including extensive datasets, reveals a major drop in the upper‐plate seismicity at a specific latitudinal area, which is not straightforward to explain.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results confirm previous studies, indicating a southward decrease in upper‐plate seismicity (Gutscher et al., 2000; Nacif et al., 2017; Rodriguez Piceda et al., 2022). However, our updated and comprehensive analysis, including extensive datasets, reveals a major drop in the upper‐plate seismicity at a specific latitudinal area, which is not straightforward to explain.…”
Section: Discussionsupporting
confidence: 93%
“…(2000) suggested that areas of flat subduction in the Andean margin release more seismic energy, thus suggesting a first‐order control of lower plate geometry on upper‐plate seismicity. In the study area, recent studies have confirmed this hypothesis, showing a decrease in seismic activity south of the Pampean flat‐slab (Lupari et al., 2015; Nacif et al., 2017; Olivar et al., 2018; Rivas et al., 2019; Rodríguez Piceda et al., 2022; Venerdini et al., 2020). This pattern of seismicity has been recently interpreted as related to changes in lithospheric strength to the south of the flat subduction segment (Rodríguez Piceda et al., 2022).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Important changes in the dip of the subducting plate may also have an impact on mantle dynamics and influence dynamic topography of the upper plate (e.g., Dávila et al., 2010; Eakin et al., 2014; Gérault et al., 2015; Liu, 2015). In addition to the subduction of bathymetric anomalies and its impact on upper‐plate processes, inherited lithospheric‐scale heterogeneities and strength contrasts in the upper plate exert first‐order controls on deformation, uplift, and magmatic processes, thus influencing the build‐up of topography in subduction orogens (e.g., Horton & Fuentes, 2016; Isacks, 1988; Rodriguez Piceda et al., 2022; Waldien et al., 2022).…”
Section: Introductionmentioning
confidence: 99%